Association of migraine with patent foramen ovale closure: A systematic review and meta-analysis. (April 2022) - Wang, Yan-Li; Wang, Fang-Ze; Zhang, Yuan; Jiang, Jiwei; Jia, Ziyan; Liu, Xiangrong; Wang, Jian; Xu, Jun
Abstract: Background: The potential correlation between patent foramen ovale (PFO) and migraine has been previously reported, but whether PFO closure plays a role in reducing migraine burden has not reached an agreement. Method: We searched PubMed, Embase, China National Knowledge Infrastructure (CNKI), Wanfang Database, VIP Science Technology Periodical Database and China Biology Medicine Database (CBM) through September 30, 2021 to identify associations between PFO closure and outcome of migraine burden. The control groups consisted of drug treatment or sham procedure. Result: Three randomized clinical trials (RCT) and 9 case-control studies were eligible for inclusion (1754 participants), of which 7 reported nonrecurrence of migraine, 4 reported reduced migraine-frequency and migraine-days, and 5 reported HIT-6 score and 4 reported MIDAS score. The mean (SD) age of participants was 40.68 (3.81) years and 1340 (76.39%) were women. PFO closure was significantly associated with a reduced risk of migraine-recurrence by 4.47 (95% CI, 2.94–6.80; I 2 = 12%), frequency of migraine by 0.35 (95% CI, 0.17–0.53; I 2 = 0%) and monthly migraine days by 0.28 (95% CI, 0.10–0.46), and decreased score of HIT-6 (SMD 1.23, 95 %CI 0.52–1.95, I 2 = 93%). Conclusion: Transcatheter PFO closure is significantly associated with burden reduction of migraine headache.